2020
DOI: 10.1038/s41598-020-69993-x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct mandibular premolar crown morphology in Homo naledi and its implications for the evolution of Homo species in southern Africa

Abstract: Homo naledi displays a combination of features across the skeleton not found in any other hominin taxon, which has hindered attempts to determine its placement within the hominin clade. Using geometric morphometrics, we assess the morphology of the mandibular premolars of the species at the enamel-dentine junction (EDJ). Comparing with specimens of Paranthropus, Australopithecus and Homo (n = 97), we find that the H. naledi premolars from the Dinaledi chamber consistently display a suite of traits (e.g., tall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…It was suggested by Davies et al. ( 50 ) that SK 96 EDJ shares similarities with Paranthropus and also approximates that of Homo naledi . The taxonomic attribution of this specimen thus remains problematic.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…It was suggested by Davies et al. ( 50 ) that SK 96 EDJ shares similarities with Paranthropus and also approximates that of Homo naledi . The taxonomic attribution of this specimen thus remains problematic.…”
Section: Discussionmentioning
confidence: 73%
“…If SK 96 belongs to Paranthropus , it differs from the morphology of P. robustus , and it raises questions regarding possible affinities with H. naledi . There is a chronological gap of more than 1 My between the Swartkrans member 2 specimen and the Rising Star Cave hominins, and phylogenetic relationships of H. naledi with other hominin taxa are still uncertain ( 50 , 65 ), and could be a focus of future studies. Our results also indicate that SK 15, holotype of the nomen oblitum T. capensis ( 15 ), as well as SK 18a that is supposedly associated with this mandible, actually represent an australopith taxon and not Homo .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, the initial intent here was to simply undertake an equivalent TSA analysis to dentally characterize H. naledi, estimate interspecific relationships, and assess its taxonomic classification. Earlier studies based on characters across the skeleton supported its inclusion in the genus Homo, but as a distinct member (Berger et al, 2015;Thackeray, 2015;Dembo et al, 2016;Irish et al, 2018; also see Holloway et al, 2018;Davies et al, 2020). A phenetic approach was deemed as most appropriate because continuous odontometric data do not lend themselves well to standard cladistic analyses; that is, they are typically reduced to a few ratios or crown areas qualitatively discretized into two or more states, along with other morphological characters (Berger et al, 2010;Strait & Grine, 2004).…”
mentioning
confidence: 99%
“…The deciduous mandibular canine and the first molars in both isomeres share apparent derived traits with the latter genus, though features of the second deciduous molars are Homo-like(Bailey et al, 2019). In a geometric morphometric study of mandibular premolar enamel-dentine junctions (EDJ),Davies et al (2020) reported that the species is closest to P. robustus in a PCA ordination of the first two components (73.7% of variation) for LP3 shape. Homo habilis is plotted nearby, but other specimens in the genus, including H. erectus and, in particular, H. neanderthalensis and H. sapiens, are increasingly distinct.…”
mentioning
confidence: 99%